Effect of Mycobacterium leprae on neurotrophins expression in human Schwann cells and mouse sciatic nerves - Maria Renata Sales Nogueira; Nádia Ghinelli Amôr; Letícia Baccaro Michellin; Milton Cury Filho; Patrícia Sammarco Rosa; Ana Carla Pereira Latini; Luciana Silva Rodrigues; Robertha Mariana Rodrigues Lemes; Flavio Alves Lara; Maria Cristina Vidal Pessolani (Memorias do Instituto Oswaldo Cruz, 2020)
BACKGROUND Although Mycobacterium leprae (ML) is well characterised as the causative agent of leprosy, the pathophysiological mechanisms underlying peripheral nerve damage still need further understanding. In vitro and in vivo studies have yielded insights into molecular mechanisms of ML interaction with Schwann cells (SC), indicating the regulation of genes and proteins crucial to neural plasticity. OBJECTIVES We aimed to investigate the effect of ML on neurotrophins expression in human SC (hSC) and mice sciatic nerves to better understand their role in leprosy neuropathy, and aiming to contribute to future therapeutic approaches. METHODS We evaluated mRNA and protein expression of BDNF, NGF, NT-3, NT-4 in hSC from amputation nerve fragments, as well as in athymic nude mice, infected by ML for eight months. FINDINGS and MAIN CONCLUSIONS Our in vitro results showed a trend to decline in NGF and BDNF mRNA in ML-treated hSC, compared to controls. The immunodetection of BDNF and NT-4 was significantly downregulated in ML-treated hSC. Conversely, ML-infected mice demonstrated upregulation of NT-3, compared to non-infected animals. Our findings indicate that ML may be involved in neurotrophins regulation, suggesting that a pathogen-related imbalance of these growth factors may have a role in the neural impairment of leprosy.